A standardized method for quantifying and characterizing repetitive head impacts in soccer matches using video footage - Porfido, T.; Caccese, J.; Gutt, J.; Wentworth, C.; Peek, K.; Bretzin, A. C.; Esopenko, C. (Science and Medicine in Football, 2022)
Soccer athletes experience repetitive head impacts (RHI) through purposeful heading and unintentional head impacts, which may be associated with acute and chronic brain injury. Previous soccer studies have sought to quantify and characterize RHI, but to-date no consistent, standardized methods exist. The Heads-Up Checklist (HUC), originally used for characterizing head impacts in hockey, was modified to be used in soccer (soccer HUC [SHUC]). Our aim was to determine the reliability of quantifying ball-to-head impacts using video verification and to develop and test the reliability of the SHUC to characterize RHI in soccer. Two trained reviewers used the SHUC to quantify ball-to-head impacts and characterize non-ball-to-head impacts in 38 male and female collegiate soccer matches. Intraclass correlation coefficient (ICC) and Cohen`s Kappa were used to assess interrater reliability. Independent t-tests and chi-square analyses were used to examine sex differences. The interrater reliability for quantifying ball-to-head impacts was excellent (ICC = 0.97); however, only half of the non-ball-to-head impact characteristics had acceptable interrater reliability with two reviewers. The number of ball-to-head-impacts and RHI characteristics were consistent between males and females (gggp > 0.05). Our results suggest that the SHUC is an applicable standardized method to quantify and characterize RHI from video footage of soccer matches; however, accurately characterizing some aspects of RHI is a challenging task that may be supplemented by head impact sensor data.